2022
DOI: 10.22146/ijc.73117
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Pharmacokinetic Properties of Compounds in <i>Hemigraphis alternata</i> (Burm.F.) T. Ander Leaves Using pkCSM

Abstract: The inflammatory process aids in healing and maintains the body's balance. Untreated acute inflammation can cause organ disease, which can lead to a chronic inflammatory phenotype. Hemigraphis alternata is a plant that has anti-inflammatory activity. The compounds contained in H. alternata leaves have been predicted to have an affinity for receptors involved in the inflammatory process. A large number of drug candidates were withdrawn from preclinical trials due to their poor pharmacokinetic profiles. Drug com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Based on this finding, compound C90 tended to be unstable when bound to blood plasma, enabling it to penetrate the membrane to display treatment effects and not induce side effects. 31,32 All compounds in this study showed low BB and PS log values. CYP2D6 and CYP3A4 were isoforms used in determining the metabolic ability of the top 5 antimalarial candidates (C2, C34, C82, C83, and C90).…”
Section: Pharmacokinetics Properties Analysismentioning
confidence: 69%
“…Based on this finding, compound C90 tended to be unstable when bound to blood plasma, enabling it to penetrate the membrane to display treatment effects and not induce side effects. 31,32 All compounds in this study showed low BB and PS log values. CYP2D6 and CYP3A4 were isoforms used in determining the metabolic ability of the top 5 antimalarial candidates (C2, C34, C82, C83, and C90).…”
Section: Pharmacokinetics Properties Analysismentioning
confidence: 69%
“…All the compounds exhibit favorable intestinal absorption in humans, as their values excedeed 30%. Each test compounds also displays commendable skin permeability, as indicated by their log Kp values being lower than −2.5 [ 30 ]. Among all the compounds, only α-mangostin is identified as substrate and inhibitor for P-glycoprotein.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…The higher the fraction of unbound drug, the less protein-bound the drug is and vice versa. 34 A compound can be interpreted as having a good distribution profile, if the log Vd value is more than -0.15, and in this case, cinnamaldehyde is predicted to have a good distribution profile with log Vd value of 0.266 L/kg. For drug metabolism, the most common reaction is oxidation and cytochrome P450 (CYP450) is the enzyme responsible for the oxidative metabolism of drugs thereby facilitating the excretion of drug metabolites and other unwanted organic compounds.…”
Section: Table 1: Results Of Molecular Docking Between Ligands (Cinna...mentioning
confidence: 99%